2014
DOI: 10.1111/echo.12624
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Helical Ventricular Myocardial Band Using Standard Echocardiography

Abstract: There is a helical ventricular myocardial band that can be observed in standard echocardiographic images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 22 publications
4
34
1
Order By: Relevance
“…This is contrary to previous findings from normal subjects [5,7]. Boettler et al [5] found similar LS on the right and on the left VS in healthy adults (n = 30, age range 18-53 years) using Doppler myocardial imaging.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…This is contrary to previous findings from normal subjects [5,7]. Boettler et al [5] found similar LS on the right and on the left VS in healthy adults (n = 30, age range 18-53 years) using Doppler myocardial imaging.…”
Section: Discussioncontrasting
confidence: 92%
“…The feasibility and reproducibility of 2D strain measurement in the present study were in agreement with previous studies [6][7][8][9][10][11]26], but feasibility was lower for the RV free wall than for the VS. For inter-observer reproducibility, the ICC showed substantial agreement on both sides of the VS and the LV, whereas the ICC for the RV free wall was modest. These results might be related to the method of image acquisition of the RV; a standard apical four-chamber view was used in order to avoid interfering with respiration of small infants.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Towards the apical doi: 10.7243/2055-091X-2-2 cone, the lateral LV wall became thinner, while the interventricular septum became thicker than that in other levels. Similar features were recorded in bovine heart [16,17]. These differences might reflect the functional or developmental species-related differences of heart structure.…”
Section: Discussionsupporting
confidence: 68%